Quality of coffee planting techniques by aerial sensors and statistical process control - Santos Santana, Lucas; Araújo e Silva Ferraz, Gabriel; Paulo Barreto Cunha, João; Bedin Marin, Diego; Lopes Bento, Nicole; de Oliveira Faria, Rafael (Revista Ciência Agronômica, 2024)
Planting is considered one most essential step in coffee growing lack of uniformity in planting may compromise future operations. Verifying planting operations quality is essential to optimize the production process and reduce costs. This study aimed to investigate planting techniques through Statistical Process Control (SPC) and aerial images. Carried out in two areas, managed manually and semi-mechanized in the Bom Jardim Farm (MG – Brazil). Data were collected through Remotely Piloted Aircraft (RPA). Quality control charts and density maps were used to identify variations in distribution and spacing between plants and between planting rows. It was verified that the planting carried out manually distributes 4.7% above the projected due to the reduction of spacing from 0.5 m to 0.48 m. The System semi-mechanized showed a deficit of 7% compared to the projected planting system and verified 0.55 m between plants. In the density map was observed that systems show the most significant planting alignment variations. Despite presenting lower results than a manual system, semi-mechanized system improvements are valid because their variations are minor around the average. Thus, points correction found limits outside can increase planting efficiency semi-mechanized.